FAKTOR PENENTU HASIL BELAJAR MAHASISWA POLITEKNIK NEGERI BANYUWANGI - Halil Halil; Kurniawan Muhammad Nur; Driyanto Wahyu Wicaksono (Journal of Social and Political Science)
The purpose of this study was to determine the effect of input factors on the grade point average (GPA). The approach used is quantitative approach with explanatory research method. The population is Poliwangi Students class of 2016 and 2017 who enter through the PMDK. The sampling technique uses simple random sampling by determining the number of samples using the Slovin equation. Data analysis used is multiple linear regressions. The results showed that the national exams and School Examinations had a significant effect on the grade point average (GPA) for students State Polytechnic of Banyuwangi class of 2016 and 2017. Department and previous Schools had no significant effect on the grade point average (GPA) students State Polytechnic of Banyuwangi class of 2016 and 2017. Keywords : grade point average (GPA), National Exams, School Exams, Departement, and Previous Schools.